Collagen from Atlantic cod (Gadus morhua) skins extracted using CO2 acidified water with potential application in healthcare - Sousa, Rita O.; Martins, Eva; Carvalho, Duarte Nuno; Alves, Ana L.; Oliveira, Catarina; Duarte, Ana Rita C.; Silva, Tiago H.; Reis, Rui L. (Journal of Polymer Research, 2020)
This work has received funding from European Union, under the scope of European Regional Development Fund (ERDF) through the Structured Project NORTE-01-0145-FEDER-000021 (Norte2020) and under the scope of the European Union Seventh Framework Programme (FP7/2007-2013) through grant agreement ERC-2012-ADG 20120216-321266 (ERC Advanced Grant ComplexiTE). PhD grant of C. O. (Norte-08-5369-000037) with financial support by Norte 2020. The authors would like to acknowledge Frigoríficos da Ermida, Lda. (Gafanha da Nazaré, Portugal) for the kind offer of Atlantic cod skins and to Dr. Manuela Pintado, Dr. Raquel Madureira and Joana Costa (Universidade Católica Portuguesa, Porto) for the use of microDSC and assistance during measurements. The authors also thank to Dr. Catarina Marques and Dr. Sandra Pina (3B’s Research Group) for assistance on XRD measurements, to Dr. Rita Lopez-Cebral (3B’s Research Group) for assistance on SEC measurements and to Dr. Alexandre Barros for discussions. The extraction of collagen from fish skins is being proposed as strategy for valorization of marine origin by-products, being a sustainable alternative to mammal collagen. The method commonly uses solutions of organic acids, but new methodologies are arising, aiming to improve process yields and/or the properties of the resulting products. In this work, skins removed from salt brine Atlantic cod (Gadus morhua) were used to extract collagen, using water acidified with CO2, obtaining an extraction yield of 13.8% (w/w). Acidified water extracted collagen (AWC) presented a total content of proline-like amino acids of 151/1000 residues, with a degree of hydroxylation of 38%, and its SDS-PAGE profile is compatible with type I collagen. Moreover, FTIR, CD and XRD results suggest the presence of preserved triple helix, having a denaturation temperature of 32.3 °C as determined by micro-DSC. AWC exhibited a typical shear thinning behavior, interesting regarding their further processing, namely in jelly-like formulations. Additionally, the ...